Band alignment of HfO2/AlN heterojunction investigated by X-ray photoelectron spectroscopy - Ye, Gang (2016)
The band alignment between AlN and Atomic-Layer-Deposited (ALD) HfO2 was determined by X-ray photoelectron spectroscopy(XPS). The shift of Al 2p core-levels to lower binding energies with the decrease of take-off angles θ indicated upward band bending occurred at the AlNsurface. Based on the angle-resolved XPS measurements combined with numerical calculations, valence band discontinuity ΔEV of 0.4 ± 0.2 eV at HfO2/AlN interface was determined by taking AlNsurface band bending into account. By taking the band gap of HfO2 and AlN as 5.8 eV and 6.2 eV, respectively, a type-II band line-up was found between HfO2 and AlN.